A million dollar idea-and your next job [intellectual property engineers]. - Kariya, S.
The legal world has many opportunities for engineers and other technically trained people. With the burgeoning of patent applications and patent-related disputes, and the greater complexity of inventions, the demand for intellectual property (IP) engineers will only increase. Some work as patent agents, which means they file patent applications on behalf of inventors and practice before the US Patent and Trademark Office (PTO); others go to law school and become patent attorneys; and still others work as examiners for the PTO, or some other country's patent office, where they analyze, research, and ultimately decide on the patentability of patent claims
Keywords: US Patent and Trademark Office; Intellectual property engineers; Legal skills; Patent agents; Patent applications; Patent attorneys; Patent-related disputes; Technical skills